2000
DOI: 10.1007/s001340051200
|View full text |Cite
|
Sign up to set email alerts
|

Plasmapheresis combined with continuous venovenous hemofiltration in surgical patients with sepsis

Abstract: Reduction in mortality in single- and double-organ failure was as high as 28% in septic patients with combined extracorporeal detoxification. A prospective randomized trial in sepsis and double-organ failure should be projected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(34 citation statements)
references
References 16 publications
0
33
0
1
Order By: Relevance
“…Pathophysiologically, plasmapheresis should interrupt the so-called "vicious circle" of the systemic inflammatory response with subsequent refractory septic shock by removing virtually all mediators from the blood [2,3,4]. However, published data of patients with sepsis or septic shock treated with plasmapheresis report either an increase [1,2,3,4] or no change [5,6] in survival rate, and until today no randomized controlled doubleblinded trial of plasmapheresis in an a priori defined homogeneous patient group such as patients with sepsis or (norepinephrine-refractory) septic shock is available. That (even repeated or continuous) plasmaphereses yielded conflicting results with regard to an improved outcome might be explained by several factors.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Pathophysiologically, plasmapheresis should interrupt the so-called "vicious circle" of the systemic inflammatory response with subsequent refractory septic shock by removing virtually all mediators from the blood [2,3,4]. However, published data of patients with sepsis or septic shock treated with plasmapheresis report either an increase [1,2,3,4] or no change [5,6] in survival rate, and until today no randomized controlled doubleblinded trial of plasmapheresis in an a priori defined homogeneous patient group such as patients with sepsis or (norepinephrine-refractory) septic shock is available. That (even repeated or continuous) plasmaphereses yielded conflicting results with regard to an improved outcome might be explained by several factors.…”
Section: Discussionmentioning
confidence: 98%
“…Plasmapheresis has been proposed as a rescue treatment in refractory septic shock [1,2,3,4,5,6]. The majority of these studies report improved outcome, possibly associated with plasmapheresis, compared to historical or no controls [1,2,3,4].…”
Section: Introductionmentioning
confidence: 99%
“…In a larger randomized study by Busund et al (43), a significantly favorable survival using plasma exchange was found. In another controlled study including 43 patients, performed by Schmidt et al (44), plasma exchange was combined with continuous venovenous hemofiltration in surgical patients with sepsis. In that study, there was a significant reduction in mortality of patients with a more extensive degree of disease, whereas this difference was not significant when including patients with less severe illness.…”
Section: Discussionmentioning
confidence: 99%
“…Of the prospective studies in which the benefit of plasma filtration has been compared with retrospective controls, two studies have shown a beneficial effect in meningococcal sepsis whereas a third study including patients with severe sepsis failed to show a difference in survival [19] .…”
Section: Discussionmentioning
confidence: 99%